N-trimethyl chitosan coated nano-complexes enhance the oral bioavailability and chemotherapeutic effects of gemcitabine. (1st December 2021) - Chen, Guanyu; Svirskis, Darren; Lu, Weiyue; Ying, Man; Li, Hongyu; Liu, Min; Wen, Jingyuan
Abstract: N -trimethyl chitosan (TMC) is a multifunctional polymer that can be used in various nanoparticle forms in the pharmaceutical, nutraceutical and biomedical fields. In this study, TMC was used as a mucoadhesive adjuvant to enhance the oral bioavailability and hence antitumour effects of gemcitabine formulated into nanocomplexes composed of poly(lactic-co-glycolic acid) nanoparticles (PLGA NPs) conjugated with d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS). A central composite design was applied to achieve the optimal formulation. Cellular uptake and drug transportation studies revealed the nanocomplexes permeate over the intestinal cells via adsorptive-mediated and caveolae-mediated endocytosis. Pharmacokinetic studies demonstrated the oral drug bioavailability of the nanocomplexes was increased 5.1-fold compared with drug solution. In pharmacodynamic studies, the formulation reduced tumour size 3.1-fold compared with the drug solution. The data demonstrates that TMC modified nanocomplexes can enhance gemcitabine oral bioavailability and promote the anticancer efficacy. Graphical abstract: Unlabelled Image Highlights: Synthesized TMC modifies the PLGA-TPGS nanocomplexes to enhance oral absorption. The central composite design model was applied to obtain the optimal formulation. The drug release mechanism is governed by anomalous diffusion. TMC led cell uptake of particles by adsorptive and caveolae-mediated endocytosis. The carrier greatly enhanced oral drug bioavailability and inhibited tumour growth.